2020
DOI: 10.1177/0306624x20969945
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Family Violence: Investigating Patterns in the Event Process of Family Violence Perpetrators

Abstract: This study is part of a larger research project that developed the event process model of family violence (FVEPM). The FVEPM was developed by applying grounded theory methods to the event narratives of 14 men and 13 women completing community-based family violence (FV) perpetrator treatment programs. The current study extends this work with the original sample, by examining the routes individual events take through the FVEPM. Three main pathways—comprising 93% of event narratives—were identified: a conflict es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, the unique nature of our sample makes it even more important that future research tests the generalizability of the FVEPM with larger and different samples, including those who perpetrate FV against non-partner family members, who characteristically use physical FV in their relationships with event victims (e.g., a high-risk sample; extension currently underway), and with a wide range of ethnicities. Furthermore, the utility of the FVEPM can be enhanced by identifying distinct pathways through the model; we report this research in Stairmand, Dixon, & Polaschek (2019). Offense (or event) process models are the foundation stone for higher levels of theory development (Polaschek, 2016), and we expect that this first attempt to construct a comprehensive event process model of FV—perpetrated by men and women toward intimate partners and other family members—will stimulate further replication and additional theoretical advances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the unique nature of our sample makes it even more important that future research tests the generalizability of the FVEPM with larger and different samples, including those who perpetrate FV against non-partner family members, who characteristically use physical FV in their relationships with event victims (e.g., a high-risk sample; extension currently underway), and with a wide range of ethnicities. Furthermore, the utility of the FVEPM can be enhanced by identifying distinct pathways through the model; we report this research in Stairmand, Dixon, & Polaschek (2019). Offense (or event) process models are the foundation stone for higher levels of theory development (Polaschek, 2016), and we expect that this first attempt to construct a comprehensive event process model of FV—perpetrated by men and women toward intimate partners and other family members—will stimulate further replication and additional theoretical advances.…”
Section: Discussionmentioning
confidence: 99%
“… 4. These differences are further explored in Stairmand, Dixon, & Polaschek (2019), in which a predominantly female pathway was found. …”
mentioning
confidence: 99%
“…Using the coding report from Stage 1, MS examined individual patterns across Section 3 (sub)categories for each event narrative. Comparing these patterns to the pathway descriptions and analysis outlined by Stairmand, Dixon, et al (2019), MS then identified whether each event narrative could be allocated to one of the three distinct pathways described in the FVEPM development study. As in Stage 1, MS routinely discussed pathway development and allocation with DP.…”
Section: Methodsmentioning
confidence: 99%
“…The current study is part of a larger research project in which we developed (Stairmand, Polaschek, et al, 2019) and examined pathways through (Stairmand, Dixon, et al, 2019) the FVEPM with a community-based treatment sample. This study further developed the FVEPM by testing the generalizability of the FVEPM (Stage 1) and its pathways (Stage 2) with an incarcerated sample of men with extensive histories of violent and other offending.…”
Section: Event-based Research and Offense Process Modelsmentioning
confidence: 99%
See 1 more Smart Citation